Upaya PT Z dalam Menjaga Profitabilitas Melalui Corporate Social Responsibility - Aaron William Junior; Dianne Frisko Koan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Corporate Social Responsibility (CSR) is a management approach that integrates sustainable values into business operations to address social and environmental well-being. Although commonly applied by large corporations, this study examines the efforts of PT Z, a Micro, Small, and Medium-sized Enterprise (MSME) in the fashion sector, in maintaining profitability through CSR implementation. Drawing on CSR and sustainability theories, as well as previous research on CSR implementation in MSMEs, this study analyzes whether and how MSMEs implement CSR and its impacts on them. Conducted through a qualitative approach with a case study, this research examines PT Z's CSR practices and the challenges they face. The findings indicate that despite understanding the concept of CSR, PT Z only implements CSR at the economic responsibility level, with activities mostly aimed at enhancing profitability. Lack of commitment and financial challenges, as well as regulations, are the main barriers to broader CSR implementation. Overall, these findings depict that MSMEs, including PT Z, tend to focus on the economic aspects of business and overlook social and environmental impacts. The implication is the need for greater awareness and support from government, stakeholders, and external resources to assist MSMEs in effectively implementing CSR. This research contributes to the CSR literature by filling the knowledge gap on CSR practices in MSMEs and providing insights into the challenges and opportunities MSMEs face in implementing CSR.